Pengaruh Perdagangan Internasional Dan Investasi Terhadap Pertumbuhan Ekonomi Indonesia - Nabila Syafitri; Hendra Ibrahim (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The more advanced a system becomes, especially in business. One form of business is trade. Due to the development of the times, the scope of trade has not only reached within the country but has touched abroad and internationally. But does this correlate smoothly with the domestic economy? So the aim of this research is to determine the influence of international trade and investment on Indonesia's economic growth. This research method uses literature study by taking references that refer to this material and is supported by previous research for further study. The results obtained are that International Trade and Investment have a significant effect on economic growth.